A Phylogenomic Analysis of the Floral Transcriptomes of Sexually Deceptive and Rewarding European Orchids, Ophrys and Gymnadenia - Piñeiro Fernández, Laura; Byers, Kelsey J. R .P.; Cai, Jing; Sedeek, Khalid E. M.; Kellenberger, Roman T.; Russo, Alessia; Qi, Weihong; Aquino Fournier, Catharine; Schlüter, Philipp M. (Frontiers in Plant Science, 2019)
The orchids (Orchidaceae) constitute one of the largest and most diverse families of flowering plants. They have evolved a great variety of adaptations to achieve pollination by a diverse group of pollinators. Many orchids reward their pollinators, typically with nectar, but the family is also well-known for employing deceptive pollination strategies in which there is no reward for the pollinator, in the most extreme case by mimicking sexual signals of pollinators. In the European flora, two examples of these different pollination strategies are the sexually deceptive genus Ophrys and the rewarding genus Gymnadenia, which differ in their level of pollinator specialization; Ophrys is typically pollinated by pseudo-copulation of males of a single insect species, whilst Gymnadenia attracts a broad range of floral visitors. Here, we present and describe the annotated floral transcriptome of Ophrys iricolor, an Andrena-pollinated representative of the genus Ophrys that is widespread throughout the Aegean. Furthermore, we present additional floral transcriptomes of both sexually deceptive and rewarding orchids, specifically the deceptive O. insectifera, O. aymoninii, and an updated floral transcriptome of O. sphegodes, as well as the floral transcriptomes of the rewarding orchids Gymnadenia conopsea, G. densiflora, G. odoratissima and G. rhellicani (syn. Nigritella rhellicani). Comparisons of these novel floral transcriptomes reveal few annotation differences between deceptive and rewarding orchids. Since together, these transcriptomes provide a representative sample of the genus-wide taxonomic diversity within Ophrys and Gymnadenia (Orchidoideae: Orchidinae), we employ a phylogenomic approach to address open questions of phylogenetic relationships within the genera. Specifically, this includes the controversial placement of O. insectifera within the Ophrys phylogeny and the placement of ‘Nigritella’-type morphologies within the phylogeny of Gymnadenia. Whereas in Gymnadenia, several conflicting topologies are supported by a similar number of gene trees, a majority of Ophrys gene topologies clearly supports a placement of O. insectifera as sister to a clade containing O. sphegodes.